Analisis Fundamental Saham Sektor Food and Beverage pada LQ45 Periode I Tahun 2020 - Annuridya Octasylva; Faisal Fachroji (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2020)
For beginners, to start investing should have careful consideration. Investment objectives, time period, risk are things that must be considered, and the most important is what investment instruments are suitable and we will choose later, of course, to achieve the objectives of the investment itself, namely future profits. Some investment instruments that have the advantages that have been summarized by the Indonesia Stock Exchange as of December 29, 2017 include, Savings (2.53%), government bonds (8.96%), gold (7.30%), deposits (7.36) %), and shares (13.13%).Technical and fundamental analysis are two analyzes that are often used to analyze stock movements. Technical analysis is an analysis that predicts future stock prices using historical prices. Whereas fundamental analysis is an analysis that uses information inside and outside the company, such as performance, business competitors, industry and even micro-macroeconomics, as well as market information. Fundamental analysis is generally used by long-term investors, so the sustainability of the company is a very important consideration.Common indicators in Fundamental Analysis are EPS (Earning Per Share), PER (Price Earning ratio), PBV (Price Book Value), ROE (Return of Equity), Dividend Yield, and DER (Debt Earning Ratio). From the fundamental analysis using the 2019 financial statements of food and beverage sector companies in LQ45 with EPS, PER, PBV, ROE, DY, and DER indicators the best performance is on UNVR company shares, because almost all indicators occupy good positions except DER indicators because UNVR has a high DER, then followed by JPFA, ICBP, and INDF. Keyword: investment, fundamental analysis, EPS (Earning Per Share), PER (Price Earning Ratio), PBV (Price Book Value), ROE (Return of Equity), Dividend Yield, and DER (Debt Earning Ratio)